Backbone thioamide directed macrocyclisation: lactam stapling of peptides. Issue 7 (1st February 2022) - Taresh, Ameer B.; Hutton, Craig A.
Abstract : The intramolecular Ag(i )-promoted reaction of peptide thioamides containing Asp and Lys residues generates the Lys–Asp (or Asp–Lys) side-chain lactam bridged peptides without requirement of a coupling agent. Abstract : A novel method for lactam stapling of Asp/Lys-containing peptides has been developed that does not require coupling agents. A backbone thioamide is incorporated at the N-terminal side of the aspartate residue. Ag(i )-promoted activation of the thioamide in the vicinity of the Asp carboxylate generates a cyclic isoimide intermediate that is trapped by the Lys amine to generate the macrolactam. This method is suitable for generation of i, i +2, i, i +3, and i, i +4-spaced lactam-bridged peptides.